Perbedaan Nilai Forman oleh Penutur Bahasa Jawa dan Batak Menggunakan Aplikasi Praat - Faninsky Hasibuan; Cynthia Siregar; T. Syarfina; Rahmadsyah Rangkuti (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2023)
One natural language is the human voice. Every human being has a variety of different voices. This diversity can be seen from the formant, pitch and volume of the sound. The voice input command is needed to find out the frequency format in the computer application, Praat. The researcher started this research by carrying out pre-processing, namely preemphasis, frame blocking and windowing, then formant values ​​could be determined using Linear Prediction. Based on the test results, the formant values ​​obtained in Javanese for F1 are in the range of 400-600, the F2 formant values ​​are in the range of 1700-2200, the F3 formant values ​​are in the range of 3300-3700, the F4 formant values ​​are in the range of 4300-4500. In the Batak language for F1 the range is 500-700, the F2 formant value is the range 1200-1500, the F3 formant value is the range 2500-3100, the F4 formant value is the range 3500-4200 Abstrak Salah satu natural language yaitu suara manusia. Setiap manusia terdapat keragaman suara yang berbeda-beda. Keragaman tersebut dilihat dari formant, pitch dan volume suara. Perintah memasukkan suara dibutuhkan untuk mengetahui forman frekuensi dalam aplikasi komputer, Praat. Peneliti mengawali penelitian ini dengan melakukan pre-processing yaitu preemphasis, frame blocking dan windowing kemudian nilai forman dapat ditentukan menggunakan Linear Prediction. Berdasarkan hasil pengujian nilai forman yang diperoleh dalam bahasa Jawa untuk F1 kisaran 400–600, nilai forman F2 kisaran 1700-2200, nilai forman F3 kisaran 3300-3700, nilai forman F4 kisaran 4300-4500. Dalam bahasa Batak untuk F1 kisaran 500–700, nilai forman F2 kisaran 1200-1500, nilai forman F3 kisaran 2500-3100, nilai forman F4 kisaran 3500-4200